A leitura como processo cognitivo: um estudo sobre as fases de leitura em crianças de 4 e 5 anos - Gomes, Juliana Paula de Oliveira (2019)
This paper considers that reading is a complex cognitive process that involves various intrapsychic activities such as perception, attention, memory, and inference. Discussions regarding the reading apprehension process often appear connected to studies and research on the writing acquisition process and are not as explored or commented as aspects of children's cognitive development in the field of education. In this regard, this research aims to understand which the theoretical bases on discussions on the cognitive processes are of reading to identify the evolutionary phases and which characteristics predominate in each stage. The study develops from the application of reading activities with children of four and five years of age, from a kindergarten class. For this, we shall conduct field research with a qualitative approach using as the data collection procedure the application of reading activities and speech records made during the activities. We based the analysis especially on the studies conducted by Ferreiro and Teberosky (1999), Maranhe (2011), Monteiro and Soares (2014), Koch (2013), Koch and Elias (2013), Solé (1998), Silva, (2003), and Smith (1989) on the perspective of reading as a cognitive process. By analyzing the activities, we identified characteristics of the reading phases and of the evolution from one phase to another in the individual development of children according to the studies of the authors selected for this work. We also identified the characteristics of the reading phases related to the development of the writing phases considering the studies conducted by Ferreiro and Teberosky (1999). The final product of this research is characterized by a lecture in extension course organized by teachers Ilsa do Carmo Vieira Goulart and Giovana Rodrigues Cabral.